China and the International Criminal Court - Zhu, Dan (Governing China in the 21st Century, 2018)
This book focuses on the evolving relationship between China and the International Criminal Court (ICC). It examines the substantive issues that have restricted China's engagement with the ICC to date, and provides a comprehensive assessment of whether these Chinese concerns still constitute a significant impediment to China's accession to the ICC in the years to come. The book places the China-ICC relationship within the wider context of China's interactions with international judicial bodies, and uses the ICC as an example to reflect China's engagement with international institutions and global governance in general. It seeks to offer a thought-provoking resource to international law and international relations scholars, legal practitioners, government legal advisers, and policy-makers about the nature, scope, and consequences of the relationship between China and the ICC, as well as its impact on both global governance and order. This book is the first of its kind to explore China's engagement with the ICC primarily from a legal perspective.